Intraband Wavelet-based coding of arbitrary triangular meshes - Toueti, Marouen; Zaid, Azza Ouled (2014 IEEE Visual Communications and Image Processing Conference, 2014)
A scalable coding scheme for three dimensional irregular meshes is proposed in this paper. Multiresolution analysis of the original triangular mesh is obtained using wavelet decomposition. A bit plane coding architecture is then performed using intra-band dependencies between wavelet coefficients. A progressive bitstream hierarchy is created making it possible to progressively reconstruct the mesh at each resolution or quality level. Experimental assessments show that the proposed codec outperforms the state-of-the-art interband mesh coding for arbitrary triangular meshes. In addition, it maintains the ability to reconstruct progressively each intermediate mesh at any resolution level.